Composición de grado: énfasis: Composición de música para cine y medios (2020)
This degree work is a compilation of all the assignments presented throughout the career of the film and media emphasis of the music career, in addition to the degree work presented in December, which consisted of the musicalization of a 10-minute short film entitled EúGENE. This music was originally composed for a classical orchestra format, in addition to the use of virtual synthesizers. The delivery format of this short film was in a 5.1 system.